Strategi Wacana Politik dalam Membangun Narasi Perubahan: Analisis Wacana Kritis Pernyataan Anies-Muhaimin Pasca Pilpres 2024 - Nofitri, Tarizka Nur Widya; Nurhayati, Nurhayati; Prihantoro, Prihantoro (Jurnal Bahasa dan Sastra, 2025)
Language use strategies in political discourse have a role in shaping public perspectives, especially in crucial moments such as presidential elections. This research aims to analyze the political strategy of language use of Anies and Muhaimin. Therefore, this research is a descriptive qualitative research with critical discourse analysis approach model of Teun A. van Dijk. The main stages of analysis include transcription of oral data, identification of text structure (macro, micro, and supra), analysis of social cognition to reveal ideology and mental representation, and study of social context that reflects power relations. This model is relevant to connect the language structure and domination strategy of the victory announcement in the 2024 presidential election. The data collection method used was orthographic transcription on the video of Anies and Muhaimin's statements on the announcement of the victory of the president and vice president from the KPU. At the data analysis stage, this research uses the political discourse and ideology analysis scheme, Teun A. van Dijk (2002; 2006) and Halliday and Matthiessen (2014). The results showed that Anies and Muhaimin used linguistic strategies to build political legitimacy and closeness to the community. The use of pronomina, declarative mood structure, as well as disclaimer and presumption strategies show that the discourse is ideologically structured in political contestation.